Follow-up of severely injured patients can be embedded in routine hospital care: results from a feasibility study. Issue 2 (15th March 2022) - Wake, Elizabeth; Brandenburg, Caitlin; Heathcote, Kathy; Dale, Kate; Campbell, Don; Cardona, Magnolia
ABSTRACT: Objective: Understanding the longitudinal patient experience outcomes following major trauma can promote successful recovery. A novel, hospital-led telephone follow-up program was implemented by a multi-disciplinary clinical trauma service team at a Level I trauma center. This process evaluation examined what factors promoted or impeded the program's implementation. Methods: A prospective convergent mixed-methods process evaluation design was used. Quantitative data included patient and injury demographics and program feasibility data such number of telephone calls attempted/completed and call duration. Qualitative data consisted of semi-structured interviews with program participants (staff, patients, and caregivers) who had participated in the program. Descriptive statistics and thematic analysis were applied to quantitative and qualitative data, respectively. Data were collected concurrently and merged in the results to understand and describe the implementation and sustainability of the program.274 major trauma patients (ISS ≥ 12) were eligible for follow-up. A response rate of over 75% was achieved, with nurses responsible for most of the calls. Limited time and competing clinical demands were identified as barriers to the timely completion of the calls. Results: Participants valued the preexisting trauma service/patient relationship, and this facilitated program implementation. Clinicians were motivated to evaluate their patient's recovery, whilst patients felt 'cared for' and 'not forgotten' post-hospital discharge. Teamwork and leadership were highly valued by the clinical staff throughout the implementation period as ongoing source of motivation and support. Staff spontaneously developed the program to incorporate clinical follow-up processes by providing guidance, advice, and referrals to patients who indicated ongoing issues such as pain or emotional problems. Conclusion: Telephone follow-up within a clinical trauma service team is feasible, accepted by staff and valued by patients and families. Despite time constraints, the successful implementation of this program is reliant on existing clinical/patient relationships, staff teamwork and leadership support.